2010
DOI: 10.1038/cdd.2009.209
|View full text |Cite
|
Sign up to set email alerts
|

Type 3 inositol 1,4,5-trisphosphate receptor negatively regulates apoptosis during mouse embryonic stem cell differentiation

Abstract: Ca 2 þ signals generated by inositol 1,4,5-trisphosphate receptors (IP 3 Rs) are crucial for cellular processes such as apoptosis and differentiation. However, the exact roles of IP 3 Rs and their contributions to Ca 2 þ signals in pluripotent embryonic stem (ES) cell behaviors remain largely unknown. In this study, we showed that the expression of type 3 IP 3 R (IP 3 R3) was transiently downregulated with a concomitant increase in apoptosis at the early differentiation stage of murine ES cells. Knockdown of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Interestingly, we found that all of these genes are constitutively upregulated during cardiac differentiation ( Figure 2A, Table 4). This expression pattern is similar to the expression patterns of genes related to the cardiac lineage decision, such as Flk-1, Nkx2.5, Mef2c, and cardiac specific marker Ncx1, as found in our previous [40,41] and present data ( Figure 1C), suggesting that these KDMs may be involved in lineage determination.…”
Section: Discussionsupporting
confidence: 65%
“…Interestingly, we found that all of these genes are constitutively upregulated during cardiac differentiation ( Figure 2A, Table 4). This expression pattern is similar to the expression patterns of genes related to the cardiac lineage decision, such as Flk-1, Nkx2.5, Mef2c, and cardiac specific marker Ncx1, as found in our previous [40,41] and present data ( Figure 1C), suggesting that these KDMs may be involved in lineage determination.…”
Section: Discussionsupporting
confidence: 65%
“…Immunoblot analyses were performed according to the protocol described previously [45]. Protein samples were size fractionated www.cell-research.com | Cell Research Nan Cao et al 235 npg by SDS-polyacrylamide gel electrophoresis and the separated proteins were electrophoretically transferred to polyvinylindene difluoride membranes (Bio-Rad, Hercules, CA, USA).…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…mTORC2 could promote post-natal heart growth and maintain heart function in mice by synergistically interacting with PDK1 35. It is known that spontaneous apoptosis occured during the process of differentiation 36. mTORC2 was proved to be associated with apoptosis in osteosarcoma cell and breast cancer 37, 38.…”
Section: Discussionmentioning
confidence: 99%